Molecular modeling analyses of functionalized cellulose - Hend A. Ezzat; Nayera M. El‑Sayed; Dina Shehata; Hanan Elhaes; Asmaa Ibrahim; Haitham Kalil; Medhat A. Ibrahim; Moataz M. Yousef; Ibrahim S. Yahia; Heba Y. Zahran; Islam Gomaa (Scientific Reports)
Abstract Functionalization of cellulose with nanomaterials and functional groups is essential for enhancing its properties for specific applications, such as flexible sensors and printed electronics. This study employs Hartree Fock (HF) and Density Functional Theory (DFT) calculations to investigate the vibrational spectra of cellulose, identifying DFT: B3LYP/3–21 g** as the optimal model aligning with experimental spectra. Using this model, we examined the impact of functionalizing cellulose with various groups (OH, NH2, COOH, CH3, CHO, CN, SH) and graphene oxide (GO) on its electronic properties. The results indicate that cellulose functionalized with GO (Cellulose-GO) has the lowest bandgap energy (0.1687 eV), and improvements in reactivity, stability, and electronic properties were confirmed through Molecular Electrostatic Potential (MESP) and Total Dipole Moment (TDM) analyses. The spectrum of Density of States (DOS) for the cellulose functionalized with different groups shows several peaks, indicating various energy levels where electronic states are concentrated. The Projected Density of States (PDOS) analysis reveals how different functional groups affect the electronic structure of cellulose. Moreover, the (Cellulose-GO) composite was characterized using an Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) spectrometer, revealing interaction through the OH group of CH2OH, as indicated by a new band at 1710 cm−1, consistent with theoretical predictions. Overall, this study demonstrates that functionalization with GO enhances cellulose’s responsiveness, degradation, and electrical properties, making it suitable for applications in flexible electronic devices and protective barriers against corrosion.